L’émergence d’un autre ornement Art nouveau au tournant des années 1910 - Aurélien Locatelli (Les Cahiers de l'École du Louvre)
The participation of Henriette Grandjean-Bourquin (1887–1968) in the art nouveau movement of the mountains of Neuchâtel, known as“style sapin” (fir-tree style), was little-known. After having honed her technical skills in Germany and France, Grandjean-Bourquin became interested in pottery and produced a series of eighty-two glazed terracotta pieces at the Liotard de Ferney-Voltaire workshop at the end of 1911. The pieces, very well-documented in the workshop archives, bear witness to a unique production that helped combine the popular arts with new motifs inspired by the stylisation of pine trees, snowflakes and alpine flowers. In her skilful work, which attempted to give an account of the invisible forces that governed nature, it is possible to see the evolution of ornamentation in the 1910s towards a rigorous, geometric style.